Investigating the influence of network effects on the mechanism of disruptive innovation - Eko Agus Prasetio (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Disruptive technology theory receives a lot of attention and has a significant influence on scholars and managers in approaching technology competition. Some studies have formalized the disruptive technology, investigating the mechanism and determinants of disruption. While some modern technologies are understood to be disruptive, they also exhibit increasing return to the adoption properties or network effects. However, how the network effects influence the disruption mechanism has only received little attention in the previous formal disruptive technology models. Therefore, in this study, we developed a formal model to investigate the dynamics of disruption by exploring the interaction of technology development, the consumer's choice, firm's decision, and structure of demand under the influence of different degrees of network effects. The model is simulated using agent-based software of the Laboratory for Simulation Development (LSD). We argue that weak network effects allow for different competitive outcomes (i.e., competitive isolation, convergence, and disruption), where the heterogeneity of the consumers' preferences matters in determining the outcomes. Therefore, this study suggests that weak network effects enhance the likelihood of disruptive innovation, depending on the heterogeneity in customer preference. Strong network effects, however, lead to a winner-takes-all situation regardless of the heterogeneity in the consumers' preferences.
Keywords: 650; complex network; disruptive innovation; network effect; network structure